Asymmetry and Aggregation in the EU - Mayes, D.; Virén, Matti; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
This book presents a clear exposition of what constitutes asymmetry in economics. It provides an empirical application of these ideas in the case of the EU. In particular, it shows how important asymmetry is for the appropriate design of policy in the Euro Area.
Keywords: Economic policy; International relations; Macroeconomics; International economics; Political economy; Economics; Economic Policy; International Relations; Macroeconomics/Monetary Economics//Financial Economics; International Economics; International Political Economy; Political Economy/Economic Systems